An Assessment of Operational Risk Disclosure and Financial Performance of Listed Financial Institutions in Nigeria - Niyi Solomon Awotomilusi; Muyiwa Emmanuel Dagunduro; Samuel Ajibade Dada; Oluyinka Isaiah Oluwagbade (Migration Letters, 2023)
This study was prompted by the observed decline in the performance of listed financial institutions in Nigeria. Its primary objective was to assess how disclosing operational risks affects the financial performance of these institutions listed on the Nigerian Exchange Group (NGX). The research employed ex-post facto and panel data research designs, using data extracted from the audited financial statements of listed financial institutions over a ten-year period from 2012 to 2021. The study focused on a population of thirty-four listed financial institutions, including nineteen deposit money banks and fifteen insurance companies on the NGX. A purposive sampling technique was applied, investigating twenty of these firms due to the availability of complete data. The descriptive statistic and panel regression analysis were adopted. The findings of the study suggest that operational risk disclosure plays a significant role in influencing the financial performance of listed financial institutions in Nigeria. Notably, specific types of risk disclosure, such as those related to technology, reputation, and strategic risks, have a positive impact on key financial metrics. Therefore, the study underscores the importance of comprehensive operational risk disclosure, particularly in areas like technology, reputation management, and strategic planning, for financial institutions seeking to enhance their financial performance and market perception.